Reletionship Between the Physico-Chemical Properties and Different Types of Erosion on Marl Soils South of Tehran, Iran - Varavipour, Maryam; Asadi, Toraj; Arzjani, Zahra (Asian Journal of Chemistry, 2010)
Marls in arid lands are greatly erodable regions originating sediment in these lands. These type of soils are found in many part of Iran and also in several colors like gray, red and green. Erosion process in marls in lack of plant cover decreasing permeability is very active specially in marl dunes and different types of erosion specially badland is one of the distinctive properties in marl regions and there are many main and complex factors in marls erosion. The erosion in marls also depends on environmental factors like rain distribution and soil properties. The importance of marls is in type and amount of sediment that is produced and the variety of erosion forms. According to mentioned factor now-a-days effective longevity of huge dams in Iran such as Sefidroud, Save and Panozdahe khordad have been decreased and be continuously interesting for most of specialists and researchers for earth science. The study of erosion forms in marls demonstrated a direct relationship between erosion forms and some soil chemical properties and includes different sort of erosion such as sheet erosion, rill erosion and badland and the most density of rill and galley is on the marls that have high solution sodium and sodium absorption ratio (SAR). The comparing of mean physico-chemical factors of marls with different erosion forms demonstrated that the amount of Na, Mg, SAR, pH and organic carbon have significant difference in sheet, rill and badland erosion. This problem account for the role of above factors in stable and unstable of region marl and among that factors SAR value is the most important in marls that controls erosion index. The occurence of many causes of slope instability in marls formation in these regions of Iran on the one hand and lack of comprehensive research on this topic on the other hand, formed the main incentive to carry out the present paper.